Participation Income - Hiilamo, Heikki (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. This innovative book provides the first in-depth analysis of participatory income and its potential role in countering endemic poverty and unemployment in high-income countries. Heikki Hiilamo reviews the concept of basic income and specific basic income experiments before presenting participatory income as a viable alternative in the fight against poverty.